Pathogenetic Treatment of Gonarthrosis Using Autogenic Growth Factors - Nematov Dilshod Amrilloyevich (Researchparks Publishing, 2022)
In 25% of cases, therapy leads to the development of unwanted drug reactions, and in 5% of patients it can be life-threatening. Long-term use of NSAIDs often exacerbates the course. To reduce the dose or completely cancel NSAIDs, chondroprotectors, glucosamine and chondroitin sulfate, are included in the complex therapy of OA. With the ineffectiveness of NSAIDs and local forms of OA, intra-articular injections of hyaluronic acid preparations are justified. They are able to stimulate the production of endogenous HA, have anti-inflammatory, regenerative and chondroprotective effects. Stimulation of the production of endogenous HA can also be achieved by intra-articular administration of the patient's autoplasma enriched with platelets (AutoPRP). Platelet autogenous growth factors, in particular, transforming growth factor beta TGF-β, can achieve suppression of destruction processes in the joint [1.3.5.7.9.11].